Comparison Analysis Of Engine Performance Using I-Vtec System And Engine Without I-Vtec System Honda Cr-V - SUHARDI, JONAS; , Ir. Sartono Putro, MT; , Nur Aklis, S.T., M.Eng (2014)
Vehicle manufactures develop technology which can increase of performance and the engine can have a great power and torque. One of this technology is using Intelligence Variable Timing and Lift Electronic Control (i-VTEC) that can be used to solve problem above because it can control timing valve. i-VTEC can increase engine performance that can make the gasoline engine will increase power and torque. The aim of this research is to compare power and torque on active i-VTEC and non-active i-VTEC system on Honda CRV. This test was done by installing Honda CR-V 2.4 with active i-VTEC and non-active i-VTEC on Dynamometer. The Dynamometer presented the data of power and torque based on engine rotation. The result from Dynamometer test showed that maximum torque from engine use active i-VTEC is 211.7 Nm at 4900 Rpm and maximum torque from engine non-active i-VTEC is 202.8 Nm at 5350 Rpm. The engine torque using active i-VTEC is 3.67% higher than non-active i-VTEC engine. The maximum power from engine use active i-VTEC system is 181.5 Hp at 6910 Rpm and maximum power from engine non-active i-VTEC system is 167.7 Hp at 7020 Rpm. The engine power using active i-VTEC is 9.33% higher than non-active i-VTEC engine. I-VTEC organizes timing of valve which can make overlapping on the machine. Overlapping make number of air fuel mixture in combustion chamber will increase which can make performance will increases.